Comparison of active versus expectant management on fetomaternal outcome in patients with placenta previa - Arthi P., Nivedhana; R., Durga; B., Jalakandan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Placenta previa is one of the leading cause (31%) of obstetric hemorrhage. It accounts for significant maternal and perinatal morbidity and mortality. The objective of the present investigation was to compare the effect of active management versus expectant management on maternal and fetal outcome in patients with placenta previa. Methods: This randomized prospective cohort study was conducted on 100 Patients of 32 weeks to 36 weeks of gestation with diagnosis of Placenta previa. Selected patients were randomly divided into Group A- Active management and Group B - Expectant management. Results: In both the groups, majority of women were in the age group of 26-30 years and were multigravidas. The need for blood transfusion and the mode of delivery were similar in both the groups. Group A had higher incidence of PPH (22% vs 10%) and peripartum hysterectomy (18% vs 2%) when compared to group B. The maternal deaths were more in group A (4% vs 2%). Majority of the babies born to group A mothers had a low Apgar, birth weight below 2 kgs and greater NICU admission. The perinatal deaths were more in group A (16% vs 2%) and the difference was statistically significant. Conclusions: The expectant management protocol was concluded to be a better mode of management protocol in patients with placenta praevia, who are either asymptomatic or with mild to moderate bleeding.